Alcohol abuse may increase the risk of autoimmune connective tissue disease: a nationwide population-based cohort study - Chang, Chi-Chen; Wang, Chia-Ti; Shih, Hong-Mo; Ho, Chung-Han; Hsu, Chien-Chin; Lin, Hung-Jung; Chiu, Yen-Wei; Huang, Chien-Cheng (Frontiers in Psychiatry, 2024)
Objectives Altered immune and inflammatory responses resulting from alcohol abuse have been implicated in increasing the risk of autoimmune connective tissue disease (ACTD). However, limited research has been conducted on this topic in the Asian population. Therefore, this study was undertaken to investigate and address this knowledge gap. Methods Using data from Taiwan’s National Health Insurance Research Database, we identified all patients with alcohol abuse between 2000 and 2017. We selected a comparison cohort without alcohol abuse, matching them in terms of age, sex, and index date at a 3:1 ratio. We collected information on common underlying comorbidities for analysis. Both cohorts were followed up until the diagnosis of ACTD or the end of 2018. Results A total of 57,154 patients with alcohol abuse and 171,462 patients without alcohol abuse were included in the study. The age and sex distributions were similar in both cohorts, with men accounting for 89.8% of the total. After adjusting for underlying comorbidities, patients with alcohol abuse had a higher risk of developing ACTD [adjusted hazard ratio (AHR): 1.12, 95% confidence interval (CI): 1.01–1.25]. The stratified analysis revealed that this increased risk was specific to the male population. Additionally, besides alcohol abuse, liver disease, renal disease, coronary artery disease, and chronic obstructive pulmonary disease were identified as independent predictors for ACTD. Conclusion This study demonstrates that alcohol abuse increases the risk of developing ACTD in the Asian population, particularly among men. Therefore, it is important to implement alcohol cessation, especially in individuals with liver disease, renal disease, coronary artery disease, and chronic obstructive pulmonary disease.